A Comparison of Osteoblast Cell Proliferation and Osteocalcin Expression in Cuttlefish Bone and Bovine Bone Xenograft - Komang Agung Irianto; Ameria Pribadi; Ilham Abdullah Irsyam; Yudhistira Pradnyan Kloping; Oen Sindrawati (Molecular and Cellular Biomedical Sciences, 2019)
Background: Cuttlefish bone Xenograft, calcium phosphate (CaP)-based biomaterial graft, offers an alternative and has been accepted for osteoconductive and probable osteo-inductive attributes. This study aims to compare the bone healing potential between the bovine-derived (BHA) and cuttlefish bone-derived (CHA).Materials and Methods: The study compared osteoblast cell proliferation of 27 New Zealand rabbits in 2.5 mm bone defect made in the femoral bone. The samples were divided into three groups, which were control, BHA and CHA group. The chemical and physical characteristics of BHA and CHA were determined for the content of hydroxyapatite by FourierTransform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD), then tested by Scanning Electron Microscopy (SEM) to evaluate the porosity. In the end of the second week, histopathologic and immunohistochemistry examinations were performed to evaluate the amount of osteoblast and osteocalcin expression.Results: The FTIR, XRD and SEM analysis showed both BHA and CHA samples were hydroxyapatite according to Joint Committee on Powder Diffraction Standards (JCPDS). The CHA was significantly higher (297.22±19.772) compared to BHA (258.22±30.926) and control (131.67±34.213). Osteocalcin expression in CHA (7.82±2.230) compared to BHA (6.09±3.724) and control (4.07±3.606), was not significant (p>0.05). Conclusion: CHA group has the highest osteoblast cell proliferation and osteocalcin expression, meaning has a good potential as future source of bone graft.Keywords: cuttlefish bone, bovine, bone graft, osteoblast cell